HANNAH ARENDT the illegitimacy of violence. - Jahanbegloo, Ramin (ROUTLEDGE, 2025)
This book presents an original understanding of Arendt in the context of comparative political theory. The author discusses Arendt's acute and perceptive view of violence as well as practical applications of her thought in a comparative context. The book examines Hannah Arendt's ideas about politics and violence provoked by the horrors of totalitarianism. It applies the rich potential of Arendt's insights to the wider cultural context and discourse of nonviolence. Through case studies of India and Iran, it presents a new way of reading Arendt's understanding and critique of violence beyond the simple analysis of her work on power and violence. An original, nuanced and meaningful guide to Hannah Arendt, the book will be essential reading for students and scholars in politics, philosophy and peace and conflict studies.